THE PRAGMATIC FEATURES OF BRITISH AND AMERICAN SLANGS IN MODERN LINGUISTICS (International Conference on Medical Science, Medicine and Public Health, 2025)
This study explores the pragmatic features of British and American slang within the context of modern linguistics. Drawing on sociolinguistic and pragmatic theories, it investigates how slang functions in communication to express identity, establish group membership, and convey attitude. Using examples from social media, pop culture, and spoken discourse, the study highlights key differences and similarities between British and American slang usage. The findings reveal that while both varieties serve similar pragmatic functions, they differ in form, tone, and socio-cultural associate.